Gas separation performance of thin film nanocomposite membranes incorporated with polymethyl methacrylate grafted multi-walled carbon nanotubes - Wong, K. C. (Elsevier, 2015)
Recently, membrane technology has gained much momentum in the field of carbon capture and storage due to its practicality and energy efficiency. In this work, thin film nanocomposite (TFN) membranes embedded with polymethyl methacrylate (PMMA) grafted multi-walled carbon nanotubes (MWNTs) were successfully fabricated. The effects of nanofillers modification on the resultant membranes morphology and gas separation performance have been highlighted. TFN incorporated with milled PMMA grafted MWNTs showed 29% increment in CO2 permeance at 70.5 GPU with 47% and 9% enhancement in CO2/N2 and CO2/CH4 selectivity, respectively compared to the thin film composite counterpart. While the improvement was mainly attributed to the presence of highly diffusive channels upon the addition of MWNTs, PMMA grafting also played an important role in ensuring well nanofillers dispersion and good compatibility with the polyamide thin film. Uncovering the construct of membrane fabrication could pave facile yet versatile way for the development of effective membranes for greenhouse gas removal